PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR FISIKA SISWA PADA MATERI FLUIDA DI KELAS XI IPA SMA NEGERI 1 PADANGSIDIMPUAN - Rini Anggraini Pakpahan (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2019)
This research aimed to determine the effect of STAD cooperative learning model to student learning outcomes in the subject matter of fluid at class XI IPA SMA Negeri 1 Padangsidimpuan. This was eksperimental research with One Group Pretest Posttest Design. The population was all class XI IPA SMA Negeri 1 Padangsidimpuan (128 students) and sample was taken through cluster random sampling, so the sample was 32 students. The instrument of this research was the achievement test. The result of this study indicated that student learning outcomes using STAD cooperative learning model (74,69) were higher than student learning outcomes using convensional learning model (62,25). Based on the  result of hypothesis testing at significance level 5% with degree of freedom 31, tcount = 9,79 > ttable = 1,698 then the hypothesis can be accepted, it means that there was influence STAD cooperative learning model to student learning outcomes in the subject matter of fluid at class XI IPA SMA Negeri 1 Padangsidimpuan.